Profile-oriented algorithms teaching: a proposed methodology to elementary school - Moreira, Fernando (2015)
One of the first challenges in the programming field, apart from ones related to the traditional teaching methods, is the introduction of technological tools that can help improving children's learning experience by presenting them with the most appropriate problems according to their ages. This choice is of great importance since it allows students to develop their capacity of abstraction in a natural way. Moreover, it also improves students' creativity and problem-solving abilities. In order to overcome these challenges, we propose a methodology based on VARK questionnaire that defines the students’ profile and, consequently, what are the most appropriate educational materials based on technologies. Once the students’ profiles are defined it is suggested the use of Scratch programming language to develop the student’s skills on the resolution of problems through the following concepts: sequencing, repetition and conditions.